2019
DOI: 10.1016/j.rmed.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between handheld and clinic-based spirometry measurements in asthma patients receiving beclomethasone

Abstract: Introduction: Handheld spirometers for home use by patients allow longitudinal spirometry data to be collected daily and may overcome some of the limitations of in-clinic spirometry (long intervals between measurements, results can be affected by site-based coaching and patient's asthma status during a given visit). Objectives: To determine the relationship between spirometry values measured by clinic-based and handheld spirometers during a clinical trial. Methods: A post hoc correlation analysis of data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 15 publications
1
18
1
1
Order By: Relevance
“…The mSpirometry data were highly correlated with clinic spirometry. Our results concur with previous data 9 generated with other spirometry devices showing concordance between clinic and home spirometry. Furthermore, mSpirometry showed excellent repeatability over time.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The mSpirometry data were highly correlated with clinic spirometry. Our results concur with previous data 9 generated with other spirometry devices showing concordance between clinic and home spirometry. Furthermore, mSpirometry showed excellent repeatability over time.…”
Section: Discussionsupporting
confidence: 93%
“…Deploying mSpirometry measurements at home gives an option of collecting more data from the same subject without an increase in sample size or number of site clinic visits. Our limits of agreement are narrower than the previously reported results 9 …”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…It has been shown that portable spirometers linked to a mobile phone could be used as an alternative to laboratory spirometry and performed in the office or at bedside prior to discharge. 1317 In this study, we propose an active screening strategy for hospitalized smokers to improve the diagnosis of COPD, especially when there is limited accessibility to laboratory spirometry. Briefly, all hospitalized patients with risk factors for COPD (smokers aged ⩾40 years) admitted to the pulmonary and the cardiology departments were questioned on their symptoms and comorbidities and underwent spirometry with the use of a portable spirometer.…”
Section: Introductionmentioning
confidence: 99%